ПРОБЛЕМИ ВДОСКОНАЛЕННЯ БЮДЖЕТНОЇ ПОЛІТИКИ ДЕРЖАВИ В КОНТЕКСТІ ФІСКАЛЬНОЇ ДЕЦЕНТРАЛІЗАЦІЇ (Світ фінансів, 2017)
Кізима Т. О., Лободіна З. М. Проблеми вдосконалення бюджетної політики держави в контексті фіскальної децентралізації. Критично оцінено бюджетну, податкову й адміністративно-територіальну реформи в Україні. З’ясовано, що поряд із позитивними результатами модернізації бюджетних відносин багато проблем залишились невирішеними і негативно впливають на функціонування бюджетної сфери та знижують ефективність бюджетної політики держави. Наголошено на ключових проблемах, пов’язаних із запровадженням програмно-цільового методу у бюджетний процес на місцевому рівні та фінансуванням державної регіональної політики. Надано рекомендації щодо удосконалення бюджетного вирівнювання дохідної спроможності місцевих бюджетів, порядку надання міжбюджетних трансфертів, збільшення обсягу та диверсифікації джерел доходів місцевих бюджетів у контексті зміцнення фінансової бази органів місцевого самоврядування. Кизыма Т. А., Лободина З. Н. Проблемы усовершенствования бюджетной политики государства в контексте фискальной децентрализации.  Критически оценены бюджетная, налоговая и административно-территориальная реформы в Украине. Выяснено, что наряду с положительными результатами модернизации бюджетных отношений многие проблемы остались нерешенными и негативно влияют на функционирование бюджетной сферы, снижают эффективность бюджетной политики государства. Отмечены ключевые проблемы, связанные с введением программно-целевого метода в бюджетный процесс на местном уровне и финансированием государственной региональной политики. Даны рекомендации по совершенствованию бюджетного выравнивания доходной способности местных бюджетов, порядка предоставления межбюджетных трансфертов, увеличения объема и диверсификации источников доходов местных бюджетов в контексте укрепления финансовой базы органов местного самоуправления. Kizyma T., Lobodina Z. Problems of the state budget policy in the context of fiscal decentralization.Introduction. The actual problem of a state budget policy is to ensure balanced socio-economic development of the regions in order to improve the level of their financial self-sufficiency by strengthening fiscal decentralization. Fiscal decentralization increases the possibility of local authorities participation in management of assigned territory and enhances contribution to the efficient provision of population with public goods. The problem of optimal redistribution of power and financial resources between state and local authorities is one of the most important in the context of improving the efficiency of Ukraine’s budgetary system, because rationally-built and optimally-balanced system of budgetary relations serves as a guarantee of state budget policy effectiveness. Therefore an essential role and place that budget policy takes in the system of regulation of regions’ social and economic development, are making actual and necessary such thing as deepening the research of the main trends in terms of fiscal decentralization in Ukraine. Purposes. This research sets up the following purposes: to assess the impact of budget, tax and administrative-territorial reform on the budget policy as an important tool to stimulate state’s and regions’ social and economic development, and to make recommendations for its improvement in current conditions. Results. In course of this research the results of budgetary, tax and administrative-territorial reform in Ukraine were identified and evaluated. This research has found that along with the positive effects of the modernization of budget relations many problems, accumulated in the public sector, remained unresolved and continue to make negative impact on the state budget system’s functioning and reduce the effectiveness of state budget policy. Conclusion. This research proposes following conclusions and recommendations for improving an effectiveness of the state budget policy realization:– create conditions to facilitate active business operations and functioning of economic entities;– improve the calculation of basic (reverse) dotations;– review the composition of the income parts in the local budgets;– implement horizontal alignment of the revenue capacity of regional budgets solely on incomings from person income taxes;– increase professional competence and decision-making skills of the financial associates in the area of budget funds management;– increase funding for regional development by raising the exploration level for costs from state fund for regional development.